1971
DOI: 10.1039/j39710001067
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the rubiaceae of Hong Kong. Part VIII. The structure of spinosic acid A, a new triterpenoid sapogenin from Randia spinosa(Thunb.) Poir.

Abstract: Spinosic acid A, one of the sapogenins from Randia spinosa, has been shown to be 38.1 9P-dihydroxyolean-12-en-28-oic acid. Other sapogenins isolated include oleanolic acid, siaresinolic acid, and another new triterpenoid. spinosic acid B.t The sterols, p-sitosterol and stigmasterol have also been obtained. * Metastable peak observed.19-hydroxy-substituent in a P-amyrin skeleton since all the remaining possible secondary hydroxy-positions possess at least two neighbouring hydrogens and suggests that spinosic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The IR spectrum exhibited absorptions at 3419 cm -1 (-OH), 1742 cm -1 (ester carbonyl), and 1644 cm -1 (double bond). The seven tertiary methyl groups (δ 0.90 × 3, 1.10, 1.14, and 1.27 × 2) and one trisubstituted olefinic proton (δ 5.42, br s) observed in the 1 H NMR spectrum coupled with the information from the 13 C NMR spectrum (seven sp 3 carbons at δ 15.7, 33.1, 23.7, 17.5, 17.2, 28.2, and 26.1 and two sp 2 olefinic carbons at δ 122.9 and 144.2) indicated that the aglycon possessed an olean-12-ene skeleton. After an extensive 2D NMR study, the aglycon was identified as oleanolic acid.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The IR spectrum exhibited absorptions at 3419 cm -1 (-OH), 1742 cm -1 (ester carbonyl), and 1644 cm -1 (double bond). The seven tertiary methyl groups (δ 0.90 × 3, 1.10, 1.14, and 1.27 × 2) and one trisubstituted olefinic proton (δ 5.42, br s) observed in the 1 H NMR spectrum coupled with the information from the 13 C NMR spectrum (seven sp 3 carbons at δ 15.7, 33.1, 23.7, 17.5, 17.2, 28.2, and 26.1 and two sp 2 olefinic carbons at δ 122.9 and 144.2) indicated that the aglycon possessed an olean-12-ene skeleton. After an extensive 2D NMR study, the aglycon was identified as oleanolic acid.…”
Section: Resultsmentioning
confidence: 95%
“…The seven tertiary methyl groups and one trisubstituted olefinic proton observed in the 1 H NMR spectrum coupled with the information from the 13 C NMR spectrum (seven sp 3 carbons and two sp 2 olefinic carbons at δ 123.0 and 144.3) indicated that the aglycon possessed an olean-12-ene skeleton. After an extensive 2D NMR study, the aglycon was identified as siaresinolic acid . Hydrolysis of 10 with cellulase yielded the aglycon, which showed NMR data identical to those of an authentic sample .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations